Effects of topical and systemic administration of Eugenia caryophyllata buds essential oil on corneal anesthesia and analgesia - Emad Khalilzadeh; Reza Hazrati; Gholamreza Vafaei Saiah (Wolters Kluwer Medknow Publications, 2016)
Clinical studies suggest that essential oil of Eugenia caryophyllata (Clove) buds (EOEC) is efficacious in the treatment of dental pain. In the present study, we investigated the analgesic and local anesthetic effects of EOEC and its possible mechanisms of action in acute corneal pain in rats. EOEC was extracted by hydro-distillation in a Clevenger type apparatus from clove buds. The acute corneal pain was induced by applying a drop (40 µl) of 5 M NaCl solution on the corneal surface, and the numbers of eye wipes were counted during the first 30 s. The mechanical sensation of the cornea was evaluated by calibrated Von Frey filaments. Systemic administration of EOEC (100 and 200 mg/kg, SC) and morphine (2.5 and 5 mg/kg, IP) produced a significant antinociceptive effect in acute corneal pain. Pretreatment with naloxone or atropine prevented the EOEC-induced analgesia. However, L-arginine and methylene blue did not change the suppressive effect of EOEC on corneal pain response. Topical application of EOEC, eugenol and lidocaine significantly decreased corneal sensitivity. Combination treatments of eugenol (25 µg) with lidocaine (0.5%) and EOEC (50 µg) with lidocaine (0.5%) also significantly suppressed corneal sensitivity. Systemic administration of EOEC produced analgesia in the acute corneal pain through mechanisms that involved both opioidergic and cholinergic systems. In addition, topical instillation of EOEC, eugenol, and lidocaine produced local anesthesia in the rat cornea. Sub-anesthetic doses of EOEC or eugenol produced a significant local anesthetic effect when concurrently used with the sub-anesthetic dose of lidocaine.